2005
DOI: 10.7150/ijms.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of N200 and P300: Selected Studies of the Event-Related Potential

Abstract: The Event-Related Potential (ERP) is a time-locked measure of electrical activity of the cerebral surface representing a distinct phase of cortical processing. Two components of the ERP which bear special importance to stimulus evaluation, selective attention, and conscious discrimination in humans are the P300 positivity and N200 negativity, appearing 300 ms and 200 ms post-stimulus, respectively. With the rapid proliferation of high-density EEG methods, and interdisciplinary interest in its application as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
478
4
17

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 645 publications
(567 citation statements)
references
References 90 publications
45
478
4
17
Order By: Relevance
“…Our results are consistent with the previous study in Turkish subjects, in which the P300 amplitude was significantly larger in the ney (their ethical music) background than in cello (foreign music) background, and the topography of the P300 response indicated a relatively higher participation of frontal areas during hearing ney [1] . The amplitude of P300 generally was interpreted as the reflection of selective attention and memory updating process [17] , thus our experiment confirmed the inference that cultural familiar music had positive effects on selective attention and memory updating process, especially in frontal areas. The specialization of brain hemispheres for processing cultural familiar music in Chinese subjects is demonstrated by their right hemisphere lateralization.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our results are consistent with the previous study in Turkish subjects, in which the P300 amplitude was significantly larger in the ney (their ethical music) background than in cello (foreign music) background, and the topography of the P300 response indicated a relatively higher participation of frontal areas during hearing ney [1] . The amplitude of P300 generally was interpreted as the reflection of selective attention and memory updating process [17] , thus our experiment confirmed the inference that cultural familiar music had positive effects on selective attention and memory updating process, especially in frontal areas. The specialization of brain hemispheres for processing cultural familiar music in Chinese subjects is demonstrated by their right hemisphere lateralization.…”
Section: Discussionsupporting
confidence: 74%
“…LPC is the representation in working memory and was proved to relate to syntax and semantic processing [4,9,[11][12][13]17] , thus we infer that guqin music has positive effects on syntax and semantic processing in the right anterior-temporal area in Chinese subjects. On the other hand, two previous studies found that larger long-lasting positivity was caused by Thai tone [16] and Chinese music [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Most ERP research on N2 is not about language materials but usually associated with non-linguistic factors such as perceptual mismatch, attention, control and inhibition [48,49]. Different from them, the N200 reported here is hard to be attributed to these factors as it was present in one script but not in others.…”
Section: Discussionmentioning
confidence: 48%
“…Furthermore, there is an attentionrelated ERP, the N2-posterior-contralateral (N2pc), which is typically observed in the N2 time window at posterior scalp sites that are contralateral to the position of a potential target item on which attention is focused (Patel and Azzam 2005). The N2a that is elicited by deviant auditory stimuli, attended or unattended, is referred to as mismatch negativity (MMN; for a review, see Naatanen et al 2012).…”
Section: Erps For Inhibition Between 200 and 400 Msmentioning
confidence: 99%